Comparing the Effects of Aloe Vera Leaf Extract On K562 Tumor Cell and Peripheral Blood Mononuclear Cells - Minoo Shaddel (Ufuq-i Dānish, 2019)
Aims Aloe Vera is among the crucial medicinal plants, with proven anti-cancer effects. This study aimed to investigate the effect of plant extracts of Aloe Vera Leaf (AVL) on the proliferation of cell lines K562 (erythroleukemia) and Peripheral Blood Mononuclear Cells (PBMCs). Methods & Materials The inner parts of the plant, including the gelatinous substance, were emptied, and the outer layer was used to prepare the lyophilized extract. The extract was dissolved in DMSO. K562 cells and PBMCs were cultured with 9.375, 18.75, 37.5, 75, 150, and 300 μg/mL concentrations of AVL for 24, 48, or 72 hours. After cultivation, the IC50 was determined for the K562 and normal PBMCs, using the MTT assay (4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide). Doxorubicin was used as a positive control. Findings The obtained data suggested that the viability of cells in both the leukemic cell line and normal PBMCs significantly decreased by the treatment with the extract in a dose-dependent manner; however, the AVL toxicity for PBMC was significantly more than K562. IC50 for the standard drug was also significantly less than AVL extract. Conclusion AVL possesses cytotoxic effects for K562 and PBMCs. Nevertheless, it has no selective benefits and has more cytotoxic effects on PBMCs.